Structural Insights into Multi‐Metal Spinel Oxide Nanoparticles for Boosting Oxygen Reduction Electrocatalysis. Issue 8 (11th January 2022) - Kim, Jiheon; Ko, Wonjae; Yoo, Ji Mun; Paidi, Vinod K.; Jang, Ho Yeon; Shepit, Michael; Lee, Jongmin; Chang, Hogeun; Lee, Hyeon Seok; Jo, Jinwoung; Kim, Byung Hyo; Cho, Sung‐Pyo; et al.
Abstract: Multi‐metal oxide (MMO) materials have significant potential to facilitate various demanding reactions by providing additional degrees of freedom in catalyst design. However, a fundamental understanding of the (electro)catalytic activity of MMOs is limited because of the intrinsic complexity of their multi‐element nature. Additional complexities arise when MMO catalysts have crystalline structures with two different metal site occupancies, such as the spinel structure, which makes it more challenging to investigate the origin of the (electro)catalytic activity of MMOs. Here, uniform‐sized multi‐metal spinel oxide nanoparticles composed of Mn, Co, and Fe as model MMO electrocatalysts are synthesized and the contributions of each element to the structural flexibility of the spinel oxides are systematically studied, which boosts the electrocatalytic oxygen reduction reaction (ORR) activity. Detailed crystal and electronic structure characterizations combined with electrochemical and computational studies reveal that the incorporation of Co not only increases the preferential octahedral site occupancy, but also modifies the electronic state of the ORR‐active Mn site to enhance the intrinsic ORR activity. As a result, nanoparticles of the optimized catalyst, Co0.25 Mn0.75 Fe2.0 ‐MMO, exhibit a half‐wave potential of 0.904 V (versus RHE) and mass activity of 46.9 A goxide −1 (at 0.9 V versus RHE) with promising stability. Abstract : A systematic approach exploring the complex structure of multi‐metal oxide electrocatalysts is developed to obtain high‐performance oxygen reduction reaction (ORR) activity. A detailed model study of uniform‐sized Mn‐, Fe‐, and Co‐containing oxide nanoparticles reveals that the incorporation of Co tunes the geometric and electronic structure of Mn active sites, elucidating the catalytic origin of the remarkable ORR activity.